Nutritional Status is Associated with Permanent Tooth Eruption in a Group of Brazilian School Children - Caio L. B. Reis DDS, MS; Mariane C. F. Barbosa DDS, MS; Suelyn Henklein DDS; Isabela R. Madalena DDS, MS, PhD; Daniela C. de Lima DDS, MS, PhD; Maria A. H. M. Oliveira DDS, MS, PhD; Erika C. Küchler DDS, MS, PhD; Daniela S. B. de Oliveira DDS, MS, PhD (SAGE Publishing, 2021)
The present study aimed to investigate the association between nutritional status with delayed tooth eruption (DTE). Oral examination was performed in schoolchildren (8-11 years old), and DTE was defined by absence of dental gingival emergence or when primary tooth was still present in the oral cavity after the expected time. BMI z -score of each child were collected and nutritional status was defined. Chi-square test and binary logistic regression adjusted by age and gender were performed. Odds ratio (OR) and 95% Confidence Interval (95% CI) were calculated. The established alpha was 5%. Among 353 included children, 247 were classified as eutrophic, 16 as underweight, 64 as overweight, and 26 as obese. Underweight was associated as a risk factor to DTE ( P  = .014; OR = 3.5; 95% CI = 1.3-9.8), and underweight girls had more chance to present DTE than eutrophic girls ( P  = .048; OR = 4.4; 95% CI = 1.1-17.2) in chi square test. In logistic regression, underweight was associated as a risk factor to DTE (OR = 4.21; CI 95% = 1.42-12.43; P  = .009). Underweight children have a higher risk of DTE in permanents.